Emplacement setting of the granite sheeted pluton of Esperanca (Brasiliano orogen, Northeastern Brazil) - Archanjo, C. J.; Fetter, A. H. (Elsevier B.V., 2004)
Anisotropy of magnetic susceptibility (AMS) and isotopic (U-Pb, Sm-Nd) data were combined to study the emplacement setting of the granite sheets that constitute the Esperanca pluton in the Borborema Province (Northeastern Brazil). The sheets dip moderately to the SE along the contact zone between the Paleoproterozoic basement rocks and Early Neoproterozoic orthogneisses and metasediments. Granite fabrics were determined mainly using AMS in 136 sites distributed within the central and western part of the pluton. The sheets normally have susceptibility lower than 0.35 mSI but, locally, where a Ti-poor magnetite appears with titanite, the susceptibility increases up to 5 mSI. Comparison between the silicate fabric and AMS showed inconsistencies between the shape of mineral and magnetic ellipsoids despite of their orientations that fit fairly well to each other. AMS indicated the deformation was partitioned between the lower (tonalite, syenogranite) and upper (leucogranite and coarse porphyritic granite) sheets. In the lower sheets the curvilinear lineation trajectory is attributed to a dominant heterogeneous pure shear event that flattened laterally the still molten tonalite and syenogranite into the regional foliation. ne associated microstructures are typically magmatic. Zircon U/Pb data of the syenogranite yielded a crystallization age of 592 +/- 5 Ma. In the upper sheets the fabric recorded a component of simple shear deformation that displaced the coarse porphyritic granite and the top gneissic host rocks to the southwest. Microstructures are mostly of post-full crystallization type. T(DM) model ages and epsilon(Nd) (t = 0) values indicate that the magma contaminated by partial melting of the regional host rocks. Sheet propagation at the emplacement level would have exploited the contact zone between crustal blocks of different rheologies when the melt pressures would be able to tensionally fail the anisotropy of the host rocks. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: sheeted-granite; microstructure; AMS; geochronology; NE Brazil